Northeastern Asia and the Northern Rockies Treasures from the Los Angeles County Museum of Art and the Daryl S. Paulson Collection - Little, Stephen (punctum books, 2022)
The philosophical ties between Northeastern Asia and the Northern Rockies as represented in a selection of fine art - including Daoist nature deities and immortals, Confucian scholar brushes and inkstones, and Buddhist guardian kings and compassionate bodhisattvas - have never been explicated. This catalog lays the groundwork for a serious discussion of trans-Pacific acculturation: first by explaining the fundamentals of Daoism, Confucianism, and Buddhism in reference to rare works of art produced in China, Korea, and Japan between the Tang Dynasty and the Qing Dynasty, and second, by assessing the prevalence of these philosophies as indicated by photographs of temples, shrines, deities, and rituals recreated in Idaho, Montana, Wyoming, and Colorado between the Civil War and World War I. Drawing from the collections of the Los Angeles County Museum of Art and the Daryl S. Paulson Collection in Bozeman, Montana, Asian art curator Stephen Little offers three brief essays that distinguish the philosophies of Daoism, Confucianism, and Buddhism according to their founding values, each followed by several object case studies that illustrate, elaborate, and develop those ideals. Mining the photographs of the state historical societies of Boise, Helena, Cheyenne, and Denver, Euro-American art professor T. Lawrence Larkin offers a long essay that compares religious values and artistic forms on both sides of the Pacific illustrated by objects that highlight migrant and settler culture in the Inner West. Profusely illustrated with new color and rarely seen black-and-white images, and containing useful maps, chronologies, and an index, Northeastern Asia and the Northern Rockies is an invaluable reference for the general reader and an important resource for the regional scholar.